Clinical analysis of internal carotid artery aneurysm accompanied with ocular manifestations - Li, Xiao-ming; Wei, Shi-hui; Song, E; Zhou, Huan-fen (Chung-hua yen k'o tsa chih, 2010)
To study the location and size of aneurysm of internal carotid artery (AICA) with ocular manifestations and the clinical characteristic of ocular changes. Forty patients with ocular changes caused by AICA presented in Department of Ophthalmology of the General Hospital of PLA were collected and analyzed retrospectively. In 42 cases of AICA accompanied with ocular manifestations, AICA was located at paraclinoid aneurysms in 23 case and 23 cases were giant aneurysm. Visual acuity was decreased significantly in 25 cases. Oculomotor palsy was present in 21 cases. Abducens paralysis was present in 7 cases. Different degrees of visual field defects were present in 15 cases. Ocular changes in AICA include decrease of visual acuity, oculomotor palsy, abducens paralysis and various defects of visual field. Ocular changes mainly occur in paraclinoid aneurysms and giant aneurysms.